High-Entropy Alloy Laser Cladding with Cable-Type Welding Wire: Experimental Study and First-Principles Calculations - Wenjun Wang; Yifei Zheng; Zhihui Cai; Wenjian Zheng; Cai Zhang; Yu Wang; Zhiyong Zhao; Daochen Feng; Yinghe Ma; Jianguo Yang (Metals)
The Co-Cr-Fe-Ni high-entropy alloy (HEA) is particularly suitable for preparing coatings due to its excellent comprehensive properties. In this study, we use the laser cladding method to prepare Co-Cr-Fe-Ni HEA coatings with Co-Cr-Fe-Ni cable-type welding wire (CTWW) as the filling material and investigated the dilution rates of the coatings by experimental studies and first-principles calculations. The dilution rate is reduced to about 50% by changing the wire feeding speed, and a Co-Cr-Fe-Ni HEA coating with near nominal composition was prepared by multi-layer cladding. The HEA coating with near nominal composition is successfully prepared in the fourth layer of cladding. The coating is dense and uniform, with good metallurgical bonding. The mechanical properties of the coating were explored using first-principles calculations. All four coatings exhibit a single face-centered cubic (FCC) phase with good mechanical stability in the ground state. The bulk modulus B, shear modulus G, and Young’s modulus E of the four layers of coatings are gradually decreasing from B = 202 GPa, G = 136 GPa, and E = 334 GPa to B = 239 GPa, G = 154 GPa, and E = 380 GPa. The brittleness of the coating shows a trend of first decreasing and then increasing, and the coating closest to the nominal composition has the highest brittleness.